Pelanggaran Berat HAM dalam RUU KUHP: Tinjauan dari Hukum Internasional (Gross Violations of Human Rights in the Criminal Code Bill: an Overview from International Law) - Bernhard Ruben Fritz Sumigar (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2020)
The spirit of the drafter of the Criminal Code Bill (CCB) to fully codify all criminal provisions, including those relating to the gross violations of human rights, into a single legally binding instrument is marked with the inconsistency of its formula with the standard provided in numerous instruments under international law. In light of this situation, this article is presence to discuss legal challenges arising from the stipulation of gross violations of human rights under CCB. By using qualitative and descriptive normative methods, this article finds three fundamental problems between the provisions of CCB and the international legal framework. The problems in question are related to (i) the inaccuracy of the use of the term “Serious Crimes against Human Rights” in CCB, as well as misregulation of (ii) crimes of genocide and (iii) crimes against humanity in CCB with international law. On this basis, this article concludes that the provisions of gross human rights violations in CCB are contrary to the provisions of international law which are binding and applicable to Indonesia, and therefore, this article is prepared to provide recommendations for policymakers to reconsider the formulation of the provisions of gross human rights violations in CCB in order to be compatible with Indonesia’s international obligations to comply with the provisions of international law. AbstrakSemangat perumus Rancangan Undang-Undang KUHP (RUU KUHP) untuk melakukan kodifikasi total semua ketentuan pidana, termasuk yang berkaitan dengan pelanggaran berat HAM, ditandai dengan ketidak-konsistenan antara rumusan yang diatur dengan standar dalam sejumlah instrumen hukum internasional. Berdasarkan hal tersebut, artikel ini disusun untuk mendiskusikan tantangan hukum yang akan timbul dari pengaturan tentang pelanggaran berat HAM dalam RUU KUHP. Dengan menggunakan metode kualitatif dan deskriptif normatif, artikel ini menemukan 3 (tiga) permasalahan antara ketentuan RUU KUHP dan kerangka hukum internasional, yaitu (i) istilah “Tindak Pidana Berat terhadap HAM” yang tidak tepat (ii) kejahatan genosida, dan (iii) kejahatan terhadap kemanusiaan. Berdasarkan 6pembahasan, artikel ini menyimpulkan bahwa ketentuan pelanggaran berat HAM dalam RUU KUHP bertentangan dengan ketentuan hukum internasional yang mengikat dan berlaku bagi Indonesia. Oleh karena itu, artikel ini memberikan rekomendasi bagi pembuat kebijakan untuk merumuskan kembali ketentuan pelanggaran berat HAM dalam RUU KUHP agar sepadan dengan ketentuan hukum internasional.